SELF-REGULATORY CONTROL SYSTEM FOR FURNITURE FIRE - Khusanov Suban Nurullayevich; Ibragimov Islomnur (Galaxy International Interdisciplinary Research Journal, 2022)
The problem of choosing the right "air-gas" ratio to maintain the required temperature in the furnace and at the same time to achieve efficient use of fuel. A self-adjusting two-circuit fuel gas combustion scheme adapted for the methodical furnace is proposed. It was found that the automatic control system of the boiler was built on the principle of a distributed system.